Survival Risk Scores for Real-Life Relapsed/Refractory Multiple Myeloma Patients Receiving Elotuzumab or Carfilzomib In Combination With Lenalidomide and Dexamethasone as Salvage Therapy: Analysis of 919 Cases Outside Clinical Trials - Morabito, Fortunato; Zamagni, Elena; Conticello, Concetta; Pavone, Vincenzo; Palmieri, Salvatore; Bringhen, Sara; Galli, Monica; Mangiacavalli, Silvia; Derudas, Daniele; Rossi, Elena; Ria, Roberto; Catalano, Lucio; et al. (Frontiers in Oncology, 2022)
The present study aimed to develop two survival risk scores (RS) for overall survival (OS, SRSKRd/EloRd) and progression-free survival (PFS, PRSKRd/EloRd) in 919 relapsed/refractory multiple myeloma (RRMM) patients who received KRd/EloRd. The median OS was 35.4 months, with no significant difference between KRd versus EloRd arms. In multivariate analysis, advanced ISS (HR=1.31; P=0.025), the interval diagnosis-therapy (HR=1.46; P=0.001), the number of previous lines of therapies (HR=1.96; P<0.0001), older age (HR=1.72; P<0.0001), and prior lenalidomide exposure (HR=1.30; P=0.026) remained independently associated with death. The median PFS was 20.3 months, with no difference between the two strategies. The multivariate model identified a significant progression/death risk increase for ISS III (HR=1.37; P=0.002), >3 previous lines of therapies (HR=1.67; P<0.0001), older age (HR=1.64; P<0.0001), and prior lenalidomide exposure (HR=1.35; P=0.003). Three risk SRSKRd/EloRd categories were generated: low-risk (134 cases, 16.5%), intermediate-risk (467 cases, 57.3%), and high-risk categories (213 cases, 26.2%)). The 1- and 2-year OS probability were respectively 92.3% and 83.8% for low-risk (HR=1, reference category), 81.1% and 60.6% (HR=2.73; P<0.0001) for intermediate-risk, and 65.5% and 42.5% (HR=4.91; P<0.0001) for high-risk groups. Notably, unlike the low-risk group, which did not cross the median timeline, the OS medians were 36.6 and 18.6 months for intermediate- and high-risk cases, respectively. Similarly, three PRSKRd/EloRd risk categories were engendered. Based on such grouping, 338 (41.5%) cases were allocated in the low, 248 (30.5%) in the intermediate, and 228 (28.0%) in the high-risk groups. The 1- and 2-year PFS probability were respectively 71.4% and 54.5% for low-risk (HR=1, reference category), 68.9% and 43.7% (HR=1.95; P<0.0001) for intermediate-risk, and 48.0% and 27.1% (HR=3.73; P<0.0001) for high-risk groups. The PFS medians were 29.0, 21.0, and 11.7 months for low-, intermediate- and high-risk cases. This analysis showed a 2.7- and 4.9-fold increased risk of death for intermediated- and high-risk cases treated with KRd/EloRd as salvage therapy. The two categories’ combined progression/death risks were 1.3 and a 2.2-fold increase compared to the low-risk group. In conclusion, SRSKRd/EloRd and PRSKRd/EloRd may represent accessible, globally applicable models in daily clinical practice, and ultimately representing a prognostic tool for RRMM patients who received KRd or EloRd.